Beautiful city: planning for transformations of the urban landscape - Ray, Karen (AESOP, 2023)
Against the backdrop of increasing needs for compact growth, higher densities, and large scale energy provisions, planners are challenged with facilitating developments that significantly alter urban and rural landscapes. The level of change is unprecedented (and usually more irreversible) in cities, where major residential and commercial developments, and even renewable energy installations more typically associated with less urban areas, are reshaping the physical character. In rural areas, and despite mounting pressures for major technologies, beauty and the visual components of landscape are still holding substantive weight in planning judgements. The explicit and compelling engagement with landscape significantly weakens as an urban discourse, while cities and towns are experiencing levels of change that equate to that of these developments in the countryside. Using cases in Ireland where beauty and the visual landscape were determining factors in planning judgement, this paper teases apart emerging trends in decision making in both rural and urban areas and raises somewhat ethical questions on accommodating such ‘subjective’ considerations in the face of global pressures for change. Keywords : Urban Landscape, Beauty Cities, Visual
Book of proceedings: 35th AESOP Annual Congress Integrated planning in a world of turbulence, Łódź, 11-15th July, 2023